Manajemen Peningkatan Mutu Pendidikan Berbasis Sistem Kredit Semester di SMA - Fitriyanto fitriyanto; Anindtya Sri Nugraheni (Universitas Pancasakti Tegal, 2019)
This study describes comprehensively improving the quality of education (inputs, processes, outputs and outcomes) through management of improving the quality of education based on the Semester Credit System. An educational innovation that refers to the provision of facilities to students who have talent and intelligence above the average in order to be able to master many lessons in a short span of time. The implementation of the Semester Credit System program at SMA Negeri 3 Purwokerto has the aim of optimizing the development potential of students and being able to improve the quality of education comprehensively. This study uses a combination method (mixed exploratory sequential method). Data collection by observation, interview, documentation and questionnaire. Data analysis is done by giving meaning to the data collected, from the meaning of the data the authors draw conclusions. The results showed: (1) Management of improving the quality of education based on the Semester Credit System includes: planning, organizing, implementing and monitoring (2) The results of the management of improving the quality of education include: students and parents of students are satisfied, the quality of education increases as seen from the increase in academic achievement and non academic student.